Microglia activation and schizophrenia: lessons from the effects of minocycline on postnatal neurogenesis, neuronal survival and synaptic pruning - Inta, Dragos; Meyer-Lindenberg, Andreas; Gass, Peter (Schizophrenia bulletin, 2017)
The implication of neuroinflammation in schizophrenia, sustained by recent genetic evidence, represents one of the most exciting topics in schizophrenia research. Drugs which inhibit microglia activation, especially the classical tetracycline antibiotic minocycline are currently under investigation as alternative antipsychotics. However, recent studies demonstrated that microglia activation is not only a hallmark of neuroinflammation, but plays important roles during brain development. Inhibition of microglia activation by minocycline was shown to induce extensive neuronal cell death and to impair subventricular zone (SVZ) neurogenesis and synaptic pruning in the early postnatal and adolescent rodent brain, respectively. These deleterious effects contrast with the neuroprotective actions of minocycline at adult stages. They are of potential importance for schizophrenia, since minocycline triggers similar pro-apoptotic effects in the developing brain as NMDA receptor (NMDAR) antagonists, known to induce long-term schizophrenia-like abnormalities. Moreover, altered postnatal neurogenesis, recently described in the human striatum, was proposed to induce striatal dopamine dysregulation associated with schizophrenia. Finally, the effect of minocycline on synapse remodeling is of interest considering the recently reported strong genetic association of the pruning-regulating complement factor gene C4A with schizophrenia. This raises the exciting possibility that in conditions of hyperactive synaptic pruning, as supposed in schizophrenia, the inhibitory action of minocycline turns into a beneficial effect, with relevance for early therapeutic interventions. Altogether, these data support a differential view on microglia activation and its inhibition. Further studies are needed to clarify the relevance of these results for the pathogenesis of schizophrenia and the use of minocycline as antipsychotic drug.
Gesehen am 25.04.2018